DIDACTIC FOUNDATIONS FOR DEVELOPING PROSPECTIVE PRIMARY SCHOOL TEACHERS’ SKILLS IN USING NON-STANDARD TASKS (USING THE EXAMPLE OF THE SUBJECT “NATIVE LANGUAGE AND LITERACY, AND METHODS OF TEACHING IT”) (International journal of artificial intelligence, 2025)
The article examines the didactic foundations for developing prospective primary school teachers’ skills in using non-standard tasks, specifically in the context of the subject “Native Language and Literacy, and Methods of Teaching It.” The study highlights the importance of non-standard tasks in enhancing students’ creative thinking, problem-solving abilities, and active engagement in the learning process. It also explores effective pedagogical strategies that enable future teachers to integrate innovative assignments into classroom practice. The research emphasizes that mastering non-standard tasks contributes not only to improving students’ literacy and language skills but also to fostering critical and analytical thinking, adaptability, and reflective competence among future educators. The findings provide practical insights for teacher training programs, suggesting methodological approaches that ensure the development of professional competencies necessary for modern primary education.